Unveiling the communication dynamics: a comprehensive review of mobile health applications - Md Ghani, Miharaini; Osman, Mohd Nizam; Mustafa, Wan Azani; Che Lah, Noor Hidayah; Shaiful Bakhtiar, Durratul Laquesha; Mazlan, Mazrina (Semarak Ilmu Publishing, 2025)
Technology has penetrated every aspect of our lives since the pandemic ended, from work to entertainment. The seamless integration of work, leisure, and learning with portable devices highlights the criticality of instantaneous information access. This escalation of technological change has given rise to mobile health applications that offer timely alerts, easily accessible information, and a range of responsibilities. This exhaustive evaluation examines these applications using data from the WoS and Scopus index-reviewed literature. Additional responsibilities, reminders, and the dissemination of knowledge are the three primary components of this study. Critical as healthcare technology evolves are mobile health applications that have been reviewed. In addition to aiding in recall, they also furnish vital health information. Health education programmes that are technology-mediated and patient-focused align well with this. This study incorporates the most recent research on mobile health applications into the ongoing discourse. The applications' multidimensional architecture facilitates a comprehensive and intuitive healthcare experience through the provision of reminders, notifications, and information dissemination. A commitment to the most recent literature in the English language and a multimethod, multimeasure assessment underscore the significance of technology that is centred around the patient. As we incorporate these technologies, healthcare is expected to undergo a paradigm shift towards patient-centric, evidence-based practices.